STATUS OF EXCLUSIVE BREASTFEEDING AND COMMUNITY-BASED TOTAL SANITATION (STBM) ON STUNTING EVENTS IN PEAT AND THE KAPUAS RIVER - Dahliansyah .; Jurianto Gambir; Widyana Lakshmi Puspita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Abstract Background: Stunting occurs due to a lack of micro and macro nutrients which are not sufficient both in quality and quantity, and also due to the presence of chronic diseases, especially when still in the womb until the age of 2 years. The prevalence of stunting can also be caused by exclusive breastfeeding status. Giving breast milk for less than 4 months has a risk of 7.325 times greater for disrupting its development compared to toddlers more than 4 months getting breast milk. The study aimed to determine the status of exclusive breastfeeding and Community-Based Total Sanitation (STBM) with the incidence of stunting in peat soils and the banks of the Kapuas River. This type of research is an analytical design that uses a case-control design to compare the peat area with the Kapuas watershed in terms of stunting related to the risk of stunting factors. This study used a retrospective approach with a total sample of 50 case groups and 50 control groups. The data obtained will be analyzed using univariate and bivariate methods using Logistic Regression. The results showed that there was a significant relationship (p='<0.05) between exclusive breastfeeding and the incidence of stunting in peat soils and riverbanks. Toddlers who are not exclusively breastfed for 6 months on peat soils and riverbanks have 7.5 times and 3.3 times chance that stunting will occur. There is no significant relationship between Community-Based Total Sanitation and the incidence of stunting on peat soils and riverbanks (p='>0.05). However, toddlers who do not do STBM have the opportunity to experience stunting. Conclusion. There is a significant relationship between exclusive breastfeeding status and the incidence of stunting. There is no significant relationship between STBM status and the incidence of stunting.